Perbandingan Perekat pada Pembuatan Biopot dari Pelepah Sawit - Nina Veronika (Politeknik Kampar, 2023)
The utilization of oil palm fronds for producing biopots as a substitute for plastic pots is expected to help reduce plastic waste and minimize palm frond waste by creating a useful product. Biopots are made from organic materials such as oil palm fronds, combined with natural binders like tapioca flour and sago flour, which are biodegradable. The biopot production process includes several stages: raw material preparation, mixing, molding, drying, and testing. The testing process involves measuring moisture content, water absorption capacity, and pH levels. The biopots were made using oil palm fronds with five different treatments based on the composition of binder usage, namely 25, 20, 15, 10, and 5 grams. The best result was obtained from the biopot using 25 grams of tapioca flour binder in treatment P1, which had a moisture content of 9.92%, water absorption of 195.85%, and a pH of 6.2.